ESTIMATING GROUNDWATER RECHARGE THROUGH TILLS: A SENSITIVITY ANALYSIS OF SOIL MOISTURE BUDGETS AND TILL PROPERTIES IN IRELAND - Fitzsimons V.P.; Misstear B.D.R. (My University, 2006)
The study highlights the dangers of limiting recharge calculations in humid climates to meteorological and soil considerations. It highlights the importance of developing a conceptual understanding of the influence of geology on recharge mechanisms and recharge rates. Uncertainties in recharge estimates through tills are examined by a study of the available literature, combined with sensitivity analyses of soil moisture budget parameters and of hypothetical scenarios of till properties and hydraulic gradients that are realistic for Irish conditions. The sensitivity analyses demonstrate that till properties have a greater influence over recharge than the soil moisture budgeting parameters. Results are considered in terms of recharge coefficients, representing the proportion of effective precipitation that becomes actual recharge to the aquifer. The literature review identifies a range in recharge coefficients from 4% to 90% in selected field and catchment scale studies from bedrock aquifers in Ireland and the U.K. The sensitivity analyses are able to simulate a similar range in recharge coefficient of 2% to 80% by varying only till permeability, thickness and vertical hydraulic gradients. In the scenarios examined, the greatest sensitivity to vertical till permeability lies between 0.001 m/day and 0.01 m/day. The sensitivity to soil moisture budgeting parameters is much less apparent. It is concluded that this is due to the dominance of grassland in Ireland and the relatively wet summers, resulting in the limited development of soil moisture deficits by comparison with some parts of the U.K.
Keywords: GROUNDWATER RECHARGE; SOIL MOISTURE BUDGET; BASEFLOW; GLACIAL TILL PERMEABILITY; IRELAND